2019
DOI: 10.3390/bios9030102
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Optical and Electrochemical Alkaline Phosphatase (ALP) Biosensors: Recent Approaches in Cells Culture Techniques

Abstract: Alkaline phosphatase (ALP), which catalyzes the dephosphorylation process of proteins, nucleic acids, and small molecules, can be found in a variety of tissues (intestine, liver, bone, kidney, and placenta) of almost all living organisms. This enzyme has been extensively used as a biomarker in enzyme immunoassays and molecular biology. ALP is also one of the most commonly assayed enzymes in routine clinical practice. Due to its close relation to a variety of pathological processes, ALP’s abnormal level is an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 168 publications
(172 reference statements)
0
19
0
2
Order By: Relevance
“…Considering the importance of ALP assay, various methods have been used for evaluation of ALP but researchers still aim to achieve the desired level of accuracy and sensitivity. 6 With the present technique, a quantification could be done with the ALP assay itself.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the importance of ALP assay, various methods have been used for evaluation of ALP but researchers still aim to achieve the desired level of accuracy and sensitivity. 6 With the present technique, a quantification could be done with the ALP assay itself.…”
Section: Discussionmentioning
confidence: 99%
“…ALP plays a vital role in catalyzing the dephosphorylation of small molecules, proteins, and nucleic acids . Thus, the visualization of ALP activity provides a simple and effective tool for chemical biology and clinical medicine.…”
Section: Resultsmentioning
confidence: 79%
“…This is in line with the result reported in [27] where it was concluded that turmeric rhizome powder can only be medicinal when it is not consumed in large amount. It was concluded in [36] that turmeric supplement enhance the performance of broilers when used as feed additives in broiler ration at the rate of 0.75% level. In this study also, it can be concluded that turmeric rhizome powder supplemented at concentration lesser than 100g/kg of total recipe could be hepato-, and renal protective especially at 2%.…”
Section: Fig 5 the Effects Of Turmeric Rhizome Powder (Trp) Supplemented Meal At Different Percentages And Standard Drug On Ast Activity mentioning
confidence: 99%